MOTIF DAN KEPUASAN MAHASISWA DALAM MENONTON PROGRAM KICK ANDY (Analisa Teori Uses and Gratifications Pada Mahasiswa FISKOM UKSW) - Timotius Arief Nugroho; Daru Purnomo (Cakrawala Jurnal Penelitian Sosial, 2013)
Life with media seems become a routine in life. Humans continue to rely on the media to find information, entertain themselves, even getting an education. Therefore, the role of media now required to be more intelligent, trustworthy or accountable truth of the information, but can also entertain the audience. One of the most famous media is television. Since its appearance in the nation on August 24, 1964, television in Indonesia continues to grow rapidly. Options television stations also show more varied, making viewers can eventually select the program it deems suitable to its needs. Based on data, the researchers found a Kick Andy often gets a variety of awards, appreciation or positive response from the public.Researcher try to examined the motive of viewer and the level of satisfaction of this show by use students of the Faculty of Social Science and Communications from the Christian University Satya Wacana as the study population. While the sample is a student of 2008 to 2010. By using purposive random sampling technique, researchers assume the data to be obtained would be more accurate and reliable. The data obtained will be processed quantitatively through the deployment questionnaire and interview process. The result will be discussed in deskripstif-explanative.The results of this study, from 67 respondens, researchers examined as a whole and also divided according to the level of media use. In the overall and active audience, the results showed the existence of gaps in the form of dissatisfaction. While the passive spectator and momental, the results showed the existence of satisfaction. Keywords: talk shows, gratification sought, gratification obtained, the gap, the level of media use